The changing pattern of fever of unknown origin in the Republic of North Macedonia - Bosilkovski, Mile; Dimzova, Marija; Cvetkova, Marija; Poposki, Kostadin; Spasovska, Katerina; Vidinic, Ivan (Walter de Gruyter GmbH, 2019)
The study aimed to compare the etiologic spectrum of diseases causing fever of unknown origin (FUO) and methods for definitive diagnosis in a tertiary care hospital in the Republic of North Macedonia during two different time periods.